Pengujian Kuat Lentur dan Permeabilitas Terhadap Beton Porous dengan Agregat Kasar Cilopang - Rafiqan Mochammad Ghilman; Eko Walujodjati (Institut Teknologi Garut, 2023)
Concrete is a construction material that is currently very commonly used. One of the innovations made is porous concrete or non-sand concrete, which is a simple form of lightweight concrete made by removing fine aggregate. This porous concrete can be used on road pavement to prevent water run-off. This research aims to experimentally examine the mechanical properties of the flexural strength and permeability of porous concrete with various variations in the cement water factor. The coarse aggregate used for Cilopang crushed stone measures 19 mm, 12 mm, 9 mm, for the average load for each sample 19 mm 5.3, 12 mm sample 7.3 and 9 mm sample 8.6. The test specimens used for each variant were 9 concrete block specimens measuring 10 x 15 x 60 cm with different aggregates. Permeability of porous concrete with different coarse aggregate sizes, sizes 19 mm, 12 mm and 9 mm. From these results the speed of absorption is 00 : 12.31 mm/sec for aggregate size 19, 00 : 15.90 mm/sec for aggregate 12, 00 : 24.01 mm/sec for aggregate. Has met the requirements based on (NRMCA, 2011) and (ACI 522R-10).